A mixed-method investigation into international university students’ experience with academic language demands - Russell, Bruce; Barron, Christine; Kim, Hyunah; Jang, Eunice Eunhee (Frontiers in Education, 2022)
English medium of instruction postsecondary education institutions have prioritized internationalization and as a result many universities have been experiencing rapid growth in numbers of international students who speak English as an additional language (EAL) students. While many EAL students are required to submit language test scores to satisfy university admission criteria, relatively little is known about how EAL students interpret admission criteria in relation to language demands post admission and what their language challenges are. This study, situated at a large Canadian university, integrated student and faculty member focus group data with data obtained from a domain analysis across three programs of study and a reading skills questionnaire. Findings suggest that students and faculty members may over interpret admission criteria for language resulting in surprise and frustration with admission criteria for both students and faculty members. Also, students experience complex and challenging language demands in their program of study which change over time. Recommendations for increased student awareness of language demands at the pre-admission stage and a more system-wide and discipline-based approach to language support post-admission are discussed.